Air survey of the Falkland Islands Dependencies, 1955–56 - Mott, P. G. (Polar Record, 1956)
In 1955 Hunting Aerosurveys Ltd. were awarded a contract by the Colonial Office to carry out a survey of Graham Land and the South Shetland Islands. The survey was to be made by means of air photography and ground control. The base for the operation was at Port Foster, Deception Island, where an ice-free anchorage for flying boats could be expected during the summer months. The survey is to be continued in 1956–57.